Effectiveness Of Text Public Service Announcements Bone Regency: Semiotic Analysis Of Charles W. Morris - Fatimah Tahir (Palakka : Media and Islamic Communication, 2020)
This study aims to describe the ideology revealed in the Bone district government public service announcements using Charles W. Morris's semiotics. Public service announcements made by the government of Bone Regency are expected to pragmatically have an effect on the community, as with commercial advertisements. Ideology in PSA is expected to have a positive effect on recipients of PSA messages. The ideology that is understood is expected to be the attitude and behavior of the people as targets of existing PSAs. This research is a qualitative descriptive type. The data is sourced from existing texts in PSA made by the Bone district government. The data collection procedures in this study are the recording technique, listening technique, and note taking technique. and interview techniques. This research will describe the ideological effects of Bone Local Government PSA based on the work culture and work spirit tagline.